Reduced Glycemic Variability in Diazoxide-Responsive Children with Congenital Hyperinsulinism Using Supplemental Omega-3-Polyunsaturated Fatty Acids; A Pilot Trial with MaxEPAR - Skae, Mars; Avatapalle, Hima Bindu; Banerjee, Indraneel (Indi); Rigby, Lindsey; Vail, Andy; Foster, Peter; Charalambous, Christiana; Bowden, Louise; Padidela, Raja; Patel, Leena; Ehtisham, Sarah; Cosgrove, Karen E.; et al. (Frontiers in Endocrinology, 2014)
Objective: Congenital Hyperinsulinism (CHI) is a rare condition of hypoglycaemia where therapeutic options are limited and often complicated by side-effects. Omega-3-polyunsaturated fatty acids (PUFA) which can suppress cardiac myocyte electrical activity, may also reduce ion channel activity in insulin-secreting cells. PUFA supplements in combination with standard medical treatment may improve glucose profile and may reduce glycaemic variability in diazoxide-responsive CHI. Design: Open label pilot trial with MaxEPA liquid (eicosapentaenoic and docosahexaenoic acid) PUFA (3 ml/day for 21 days) in diazoxide-responsive CHI patients [https://eudract.ema.europa.eu/, EudraCT number 201100363333]. Methods: Glucose levels were monitored pre treatment, end of treatment and at follow up by subcutaneous continuous glucose monitoring systems (CGMS) in 13 patients (7 girls) who received PUFA. Outcome measures were an improved glucose profile, reduced glycaemic variability quantified by a reduction in the risk of hypoglycaemia and hyperglycaemia (glucose< 4 and >10mmol/l respectively) and safety of PUFA. All children were analysed either as intention to treat (n=13) or as per protocol (n=7). Results: Mean (%) CGMS glucose levels increased by 0.1mmol/l (2%) in intention to treat and by 0.4mmol/l (8%) in per protocol analysis (n=7). The frequency of CGMS< 4mmol/l was significantly less at the end of treatment than in the pre treatment period [556(7%) v 749(10%)]. Similarly, the frequency of CGMS>10mmol/l, was also less at the end of treatment [27(0.3%) v 49(0.7%)]. Except for one child with increased LDL cholesterol, all safety parameters were normal. Conclusions: MaxEPAR was safe and reduced glycaemic variability, but did not increase glucose profiles significantly in diazoxide-responsive CHI. The supplemental value of PUFA should be evaluated in a comprehensive clinical trial.